Long-term function of ovarian tissue transplants - Sherman J. Silber; David Silber; Natalie Barbey (Middle East Fertility Society Journal, 2012)
The long term duration of function of ovarian cortical tissue grafts is reviewed in this paper by describing cases of restoration of fertility by transplant of ovarian cortical tissue from matching donors where the recipient was in need of the transplant due to sterilizing effects of leukemia, premature ovarian failure (POF), and to reflect that it may be possible to postpone the normal time of menopause or to alleviate its symptoms.